STRUCTURAL PHASE PROCESSES IN MULTICOMPONENT METAL CERAMIC OXIDE MATERIALS BASED ON THE SYSTEM Y–Ti–Zr–O (Y2О3–TiО2–ZrO2) - Чишкала, Владимир; Литовченко, Сергей; Геворкян, Эдвин; Нерубацкий, Владимир; Морозова, Оксана (SWorldJournal, 2021)
The article investigates the synthesis processes, structural characteristics and structural-phase processes in multicomponent metal-ceramic oxide materials based on the Y-Ti-Zr-O system (Y2O3-TiO2-ZrO2), synthesis of ultra- and nanodisperse oxide powders